A Governance Perspective on Development Issues (The Presidential Address) (The Pakistan Development Review, 1999)
It is with great pleasure that I welcome you to the 15th Annual General Meeting of the Pakistan Society of Development Economists. I have had the proud privilege of being associated with this Society since its inception, initially as its Founding Secretary and member and later as its President. I have watched it flourish and helped ensure that it grows from strength to strength. In this, the last meeting of the Society with me as its President, I am really cheered by the presence of so many colleagues here, particularly as we know that we live in troubled times. But I can assure you of a frank and open discussion of the key development issues of the day. Economic growth and poverty reduction are difficult to achieve in the best of times. With decaying institutions and poor governance, these goals become an impossible dream. That is why the theme of this year’s annual meeting is “Governance, Institutional Reform, and Economic Growth”. I hope that the papers being presented and the discussions on or around this theme during these four days will indicate the way forward from the current morass. I shall not bore you with the details of the economy’s deplorable condition—most of you are familiar with them. Its deterioration is best judged by the International Country Risk Guide (ICRG) ratings for Pakistan, which are computed by weighting three elements—corruption, rule of law, and bureaucratic quality. These ratings for Pakistan in 1998 are three times what they were in 1982. This means that on a relative scale, things in Pakistan are three times as bad in 1998 as the 1982 levels.